PENGARUH DISIPLIN KERJA DAN ROTASI KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR IMIGRASI KELAS I TPI BANDAR LAMPUNG - Putri, Hermina Zulhana; Mulyawan, Budy; Febrianto, Arief (Journal of Administration and International Development, 2024)
Abstract This research aims to measure the extent to which work discipline and job rotation affect employee performance at the Class I TPI Immigration Office in Bandar Lampung. Work discipline is defined as an individual’s behavior based on work regulations, procedures, and attitudes in accordance with organizational rules, whether written or unwritten. Meanwhile, job rotation is a management strategy or approach that involves transferring or shifting employees from one position to another or to different responsibilities within the organization. The goal is to provide employees with opportunities to expand their knowledge and skills, as well as to prevent boredom, thereby fostering healthy career development. Based on observations and interviews at the Class I TPI Immigration Office in Bandar Lampung, several inconsistencies were found, including an increase in absenteeism, particularly among employees who do not arrive on time or are absent without notice. Furthermore, the implementation of job rotation has not been deemed effective. The research method used in this study is quantitative. Data collection was conducted through observations, initial interviews, and the distribution of questionnaires. The sampling technique employed was purposive sampling, and data analysis was carried out using a Likert scale. The data analysis technique applied in this research is multiple linear regression analysis. The research results indicate that work discipline and job rotation have a simultaneous and significant impact on employee performance at the Class | TPI Immigration Office in Bandar Lampung. Data collection results show that the F calculated value of 27.068 is greater than the F table value of 3.15, with a significance value of 0.000 < 0.05. The Adjusted R square value is 0.483, indicating that 48.3% of the performance variable is influenced by the independent variables, namely work discipline and job rotation. Based on the conclusions and data analysis results, it is recommended that stricter policies be implemented and supported by leadership to create a deterrent effect. Additionally, motivation and rewards should be provided to employees who adhere to the regulations set by the office.